PENGARUH PROFITABILITY, LIQUIDITY, NET WORKING CAPITAL, DAN GROWTH OPPORTUNITY TERHADAP CASH HOLDING PADA PERUSAHAAN CONSUMER NON-CYCLICALS - Gunawan, Chairull Noval; Sufiyati, Sufiyati (Jurnal Paradigma Akuntansi, 2025)
This article outlines a study that looked at the impact of profitability, liquidity, net working capital, and growth opportunity on cash holdings in consumer non-cyclical companies. The quantitative descriptive research method was applied in this study. The data used consists of yearly financial reports from consumer non-cyclical enterprises, which provide detailed information about the variables under consideration. Consumer non-cyclical companies listed on the Indonesia Stock Exchange between 2020 and 2022 are the research subjects. The testing using the F-test reveals that profitability, liquidity, net working capital, and growth opportunity collectively have a significant influence on cash holding. The t-test results indicate that profitability and net working capital are factors that positively and significantly affect cash holding, while liquidity and growth opportunity do not have a significant influence on cash holding.